High genetic and chemical diversity of wild hop populations from Central Italy with signals of a genetic structure influenced by both sexual and asexual reproduction. (March 2021) - Riccioni, Claudia; Belfiori, Beatrice; Sileoni, Valeria; Marconi, Ombretta; Perretti, Giuseppe; Bellucci, Michele; Rubini, Andrea
Highlights: High genetic polymorphism was found across wild hop populations in Central Italy. High within-among populations gene flow and clonal propagation patterns were inferred. Examined populations are genetically structured in at least five genetic clusters. Wild female flowers show greatly variable bittering and aromatic qualities. New hop cultivars could be developed by exploiting wild accessions here investigated. Abstract: In order to investigate the intraspecific diversity of wild Humulus lupulus (hop) in Central Italy, 12 populations were evaluated for their genetic polymorphism by means of 13 SSR loci together with six commercial cultivars as a reference. High levels of polymorphism were found across the populations, being 140 the number of multilocus genotypes over 159 samples analyzed. Moreover, the observed heterozygosity was higher than expected in most of the populations. High levels of gene flow were thus envisaged to occur within and among wild populations, and our sampling strategy allowed us to gain insights on the propagation modes of this species, i.e. clonal versus sexual propagation. Nevertheless, a genetic structure of populations with at least five genetically different clusters was disclosed. Private alleles were observed in both wild and cultivated hops. Chemical analysis of bittering and aromatic quality of female flowers from a subset of 8 wild populations revealed a high variability among plants, especially for essential oil components. Overall, the high variability of wild accessions here examined represent a valid source to be exploited in future breeding programs for new or improved hop cultivars development.